2023
DOI: 10.1002/admi.202202404
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of La‐Doped MoS2 Nanosheets with Tuned Bandgap for Dye Degradation and Antimicrobial Activities, Experimental and Computational Investigations

Abstract: The development of efficient catalysts with a large number of active sites, tunable bandgap, and large surface area has been very challenging. In addition, a significant bottleneck in the application of catalysts for water treatment is their dissolution under extreme conditions, such as highly acidic or highly alkaline conditions that lead to poor application of the reported materials in real‐world applications. In this study, the lanthanum (La)‐doped molybdenum disulfide (MoS2) nanosheets are reported for eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…159–161 Through DFT theoretical calculations, Mahmood et al showed that the unstable 1T MoS 2 can form a more stable heterostructure by binding with rGO nanosheets. 162 Furthermore, the synergistic effect induced by the strong interaction between rGO nanosheets and MoS 2 facilitates the interfacial faradaic charge transfer reaction, which transforms slow diffusion intercalation into fast redox reaction, resulting in long-cycle stability, high rate capability and high specific capacity. In addition, a graphene/h-BN bilayer system will enable tuning of the optical properties by regulating the band gap based on the composition and atomic configurations in the materials (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…159–161 Through DFT theoretical calculations, Mahmood et al showed that the unstable 1T MoS 2 can form a more stable heterostructure by binding with rGO nanosheets. 162 Furthermore, the synergistic effect induced by the strong interaction between rGO nanosheets and MoS 2 facilitates the interfacial faradaic charge transfer reaction, which transforms slow diffusion intercalation into fast redox reaction, resulting in long-cycle stability, high rate capability and high specific capacity. In addition, a graphene/h-BN bilayer system will enable tuning of the optical properties by regulating the band gap based on the composition and atomic configurations in the materials (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The reduced toxicity of NMs can be attributed to their unique physicochemical properties, including their small size and large surface area, which enhance biocompatibility. NMs are more hydrophobic than conventional bone grafts [ 56 , 57 ]. Primarily, NM's hydrophobic nature facilitates favorable interactions with their surroundings.…”
Section: Research Significance Of Nanomaterials In the Biomedical Fieldmentioning
confidence: 99%
“…However, there are undeniably many advanced applications that have yet to be discovered. 145 8.2. HPs QDs@COFs.…”
Section: Hps Qds@mofs-cofs Based Materialsmentioning
confidence: 99%
“…Significant progress has been made in understanding and utilizing HPs QDs@MOFs. However, there are undeniably many advanced applications that have yet to be discovered …”
Section: Hps Qds@mofs-cofs Based Materialsmentioning
confidence: 99%